Effects of Initial δ Phase on Creep Behaviors and Fracture Characteristics of a Nickel‐Based Superalloy. Issue 4 (6th December 2017) - Lin, Y. C.; Yin, Liang‐Xing; Luo, Shun‐Cun; He, Dao‐Guang; Peng, Xiao‐Bin
Abstract : Uniaxial creep tensile experiments are performed to study the influences of initial δ phase (Ni3 Nb) on the creep features and fracture behaviors of a nickel‐based superalloy. Experimental results show that the creep features and fracture behaviors of the researched superalloy are closely relevant to the volume fraction of initial δ phase. The minimum creep rate increases with the increased volume fraction of initial δ phase. The appropriate volume fraction of initial δ phase can improve the creep resistance and plasticity. So, the rupture time and the elongation to fracture initially increase, when the volume fraction of initial δ phase is relatively low, and then decrease with the increase of volume fraction of initial δ phase. Additionally, with the increased initial δ phase, the failure mode changes from a typical intergranular fracture to the mixed fracture pattern of ductile intergranular and cleavage fracture. Abstract : Effects of initial δ phase (Ni3Nb) on uniaxial creep behavior and fracture characteristics of a nickel‐based superalloy are investigated. The appropriate initial δ phase fraction can improve the creep resistance and plasticity. The increased initial δ phase changes the failure mode from a typical intergranular fracture to the ductile intergranular/cleavage mixed fracture.